COP9 signalosome-specific phosphorylation targets p53 to degradation by the ubiquitin system - Bech-Otschir, Dawadschargal (Oxford University Press, 2001)
In higher eukaryotic cells, the p53 protein is degraded by the ubiquitin–26S proteasome system mediated by Mdm2 or the human papilloma virus E6 protein. Here we show that COP9 signalosome (CSN)-specific phosphorylation targets human p53 to ubiquitin–26S proteasome-dependent degradation. As visualized by electron microscopy, p53 binds with high affinity to the native CSN complex. p53 interacts via its N-terminus with CSN subunit 5/Jab1 as shown by far-western and pull-down assays. The CSN-specific phosphorylation sites were mapped to the core domain of p53 including Thr155. A phosphorylated peptide, Δp53(145–164), specifically inhibits CSN-mediated phosphorylation and p53 degradation. Curcumin, a CSN kinase inhibitor, blocks E6-dependent p53 degradation in reticulocyte lysates. Mutation of Thr155 to valine is sufficient to stabilize p53 against E6-dependent degradation in reticulocyte lysates and to reduce binding to Mdm2. The p53T155V mutant accumulates in both HeLa and HL 60 cells and exhibits a mutant (PAb 240+) conformation. It induces the cyclin-dependent inhibitor p21. In HeLa and MCF-7 cells, inhibition of CSN kinase by curcumin or Δp53(145–164) results in accumulation of endogenous p53.